Association of changes in obesity and abdominal obesity status with early-onset colorectal cancer risk: a nationwide population-based cohort study - Song, Ji Hyun; Seo, Ji Yeon; Jin, Eun Hyo; Chung, Goh Eun; Kim, Young Sun; Bae, Jung Ho; Kim, Sunmie; Han, Kyung-Do; Yang, Sun Young (Frontiers in Medicine, 2023)
Background and aims: The incidence of early-onset colorectal cancer (EO-CRC, diagnosed before 50 years of age) has increased in recent decades. The aim of this study was to investigate the association between changes in obesity status and EO-CRC risk. Methods: From a nationwide population-based cohort, individuals < 50 years old who participated in the national health checkup program in both 2009 and 2011 were included. Obesity was defined as a body mass index ≥25 kg/m2. Abdominal obesity was defined as a waist circumference ≥ 90 cm in men and ≥ 85 cm in women. Participants were classified into 4 groups according to the change in obesity (normal/normal, normal/obese, obese/normal, persistent obese) and abdominal obesity (normal/normal, normal/abdominal obesity, abdominal obesity/normal, persistent abdominal obesity) status. Participants were followed up until 2019 and censored when they became 50 years old. Results: Among 3,340,635 participants, 7,492 patients were diagnosed with EO-CRC during 7.1 years of follow-up. The risk of EO-CRC was higher in the persistent obesity and persistent abdominal obesity groups than in the normal/normal groups (hazard ratio (HR) [95% confidence interval (CI)] = 1.09 [1.03–1.16] and 1.18 [1.09–1.29], respectively). Participants with both persistent obesity and abdominal obesity had a higher EO-CRC risk than those in the normal/normal groups for both (HR [95% CI] = 1.19 [1.09–1.30]). Conclusion: Persistent obesity and persistent abdominal obesity before the age of 50 are associated with a slightly increased risk of EO-CRC. Addressing obesity and abdominal obesity in young individuals might be beneficial in reducing the risk of EO-CRC.